Case Series of Bedside Renal Cell Carcinoma Detected by Point-of-Care Ultrasound in the Ambulatory Setting. (April 2020) - Setia, Gayatri; Kedan, Ilan
Background: Kidney and renal pelvic cancer was the sixth most common cancer in men and 10th most common in women in the United States in 2018. Renal cell carcinoma (RCC), accounts for 86% of malignancies of the kidney. RCC patients are often asymptomatic; up to 25-30% have metastases at diagnosis. Few present with the triad of gross hematuria, flank pain, and abdominal mass. In RCC patients, 36% had 2 symptoms of the triad, and 60% had gross hematuria as 1 symptom. Point-of-care ultrasound (POCUS) offers a way to identify clinically meaningful anatomic abnormalities. This case series presents 3 patients in whom routine POCUS examination performed in an outpatient cardiology clinic found asymptomatic renal masses, resulting in surgical resection and cure of early-stage RCCs.Case Presentation: Patient 1: 54-year-old female with hypertension (HTN). Two solid masses were identified with POCUS in the right kidney. Patient 2: 63-year-old male with coronary artery disease (CAD) and HTN was seen at an 8-month follow-up visit. A 6-cm mass was identified in the left kidney. Patient 3: 69-year-old male with CAD, HTN, and smoking history seen at 5-month follow-up visit. A 3-cm mass in the right kidney was identified.Conclusions: Incorporating POCUS into the routine physical examination in the ambulatory care setting may improve rates of detection and increase the pretest probability of identifying renal pathology with formal imaging studies. With minimal clinician training, earlier and increased detection of asymptomatic RCC may result in improved patient survival.